Targeted metagenomics as a tool to tap into marine natural product diversity for the discovery and production of drug candidates - Trindade, Marla; van Zyl, Leonardo Joaquim; Navarro-Fernández, José; Abd Elrazak, Ahmed (Frontiers in Microbiology, 2015)
Microbial natural products exhibit immense structural diversity and complexity and have captured the attention of researchers for several decades. They have been explored for a wide spectrum of applications, most noteworthy being their prominent role in medicine, and their versatility expands to application as drugs for many diseases. Accessing unexplored environments harboring unique microorganisms is expected to yield novel bioactive metabolites with distinguishing functionalities, which can be supplied to the starved pharmaceutical market. For this purpose the oceans have turned out to be an attractive and productive field. Owing to the enormous biodiversity of marine microorganisms, as well as the growing evidence that many metabolites previously isolated from marine invertebrates and algae are actually produced by their associated bacteria, the interest in marine microorganisms has intensified. Since the majority of the microorganisms are uncultured, metagenomic tools are required to exploit the untapped biochemistry. However, after years of employing metagenomics for marine drug discovery, new drugs are vastly under-represented. While a plethora of natural product biosynthetic genes and clusters are reported, only a minor number of potential therapeutic compounds have resulted through functional metagenomic screening. This review explores specific obstacles that have led to the low success rate. In addition to the typical problems encountered with traditional functional metagenomic-based screens for novel biocatalysts, there are enormous limitations which are particular to drug-like metabolites. We also present how targeted and function-guided strategies, employing modern and multi-disciplinary approaches have yielded some of the most exciting discoveries attributed to uncultured marine bacteria. These discoveries set the stage for progressing the production of drug candidates from uncultured bacteria for pre-clinical and clinical development.